The daily activity budgets of Long-tailed Macaque (Macaca fascicularis) at Padang Teratak Wildlife Sanctuary, Beaufort, Sabah, Malaysia - Maisa Mohammad; Anna Wong (Universiti Malaysia Sabah, 2019)
At present, the conversion of natural forests into urbanized and agricultural plantation areas are rising at an accelerated rate. Due to the loss of suitable habitats, wildlife i.e. macaques are forced to move into or nearby areas close to humans. The increased encounters between humans and macaques have led to conflicts between both when macaques utilize human resources. A preliminary study was conducted to explore the daily activity pattern of macaques based on age-sex and time in human-dominated areas (e.g. human settlements, oil palm plantation and fruit orchards). . The study was conducted in Padang Teratak Wildlife Sanctuary (PTWS) located in the district of Beaufort, eastern part of Sabah, Malaysia. Opportunistic observations were conducted along the roads encompassing seven villages in four days per month from December 2015 to January 2016. The survey was conducted in four time frames for 11 hours per day (06:00-09:00, 09:00-12:00, 13:00-15:00 and 15:00-18:00) to document behaviour of macaques with regards to the time of the day. Overall, a total of 1,462 individuals from 221 groups with total direct contact of 96 hours, 53 minutes out of 132 hours, consisting of multi-males multi-females (173 encounters), multi males (18), solitary male (28) and solitary female (2). There were 13 behavioural activities recorded and the study revealed that macaques spent most of their time for moving (28.4%), foraging (25.2%), resting (19.1%) and grooming (12.3%). Results from ANOVA showed that the daily activity patterns of each categories within age-gender varied showing there was a relation between daily activity budget and age-gender of macaques. In addition, Chi-square test indicated there were interactions between age-gender and time on daily activity. In contrast, time did not have an effect on their activity pattern. Good wildlife management practices by understanding the behaviour of macaques in human settlements near degraded forests is crucial since habitat sharing by humans and macaques raise the concern of safety and health issues. The frequent encounter between this species increases transmission of some zoonotic diseases to humans such as the malaria parasite (Plasmodium knowlesi).